The Influence Of Need For Achievement On Entrepreneurial Intention Through Entrepreneurial Attitude - Ainun Zahroh; Deni Alimaningtyas; Dika Ayu Adininggar; Galuh Aulia Pratiwi; Hanis Bachrodin; Mohammad Syukri Ghozali (Pusat Riset dan Inovasi Nasional, 2024)
Generation successor in possession spiritual values, intelligence, personality, control self, and vital skills in life public formed through role education. Progress technology information and communication has create innovation products and services that meet need man. Study This use method quantitative, namely Partial Least Squares Structural Equation Modeling (PLS-SEM), for test and validate proposed hypothesis. _ Study This use google form for collecting data on vocational school students in the district Jombang. Respondent in study This namely 356 respondents were used object study. Research result show that need for achievement can explain entrepreneurial attitude and entrepreneurial intention Furthermore need for achievement will give more influence on entrepreneurial intention, if strengthened with entrepreneurial attitude as mediator variable